2014
DOI: 10.1038/jp.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic complexity of Mitchell–Riley/Martinez–Frias syndrome

Abstract: Mitchell-Riley syndrome/Martinez-Frias syndrome (MRS/MFS) is a rare, autosomal recessive disorder with multisystem involvement and poor prognosis. Most reported cases have been associated with homozygous or compound heterozygous mutations in the RFX6 gene, a transcriptional regulatory factor for pancreatic morphogenesis. Given the limited number of reported cases, the syndrome may be under-recognized. When the particular phenotype of MFS includes a mutation on the RFX6 gene and neonatal diabetes, it has been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Most patients with neonatal diabetes do not have other congenital abnormalities [ 6 ]. The association of the particular phenotype of Martinez-Frias syndrome with a mutation on the RFX6 gene and neonatal diabetes has been called Mitchell-Riley syndrome, and it was suggested that both syndromes represent a symptom continuum or an RFX6 malformation complex [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with neonatal diabetes do not have other congenital abnormalities [ 6 ]. The association of the particular phenotype of Martinez-Frias syndrome with a mutation on the RFX6 gene and neonatal diabetes has been called Mitchell-Riley syndrome, and it was suggested that both syndromes represent a symptom continuum or an RFX6 malformation complex [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that not only PBM but also other congenital malformations are associated more often with fusiform than other CM subtypes is a novel finding and could be related to their different etiopathogenesis (1). CMs may also associate with certain genetic mutations (25,26). Unfortunately, genetic testing results were not systematically registered in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…The identification of the RFX6 gene mutation in several of these published cases supports this theory; for that reason, MRS and MFS have been collectively referred to as the RFX6 gene mutation syndrome. 1,5 The clinical heterogeneity of this syndrome makes prenatal diagnosis very difficult. However, the identification of the genetic mutation in one of the family members makes necessary accurate genetic counseling of the parents regarding its consequences and the future of the baby.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoplasia or aplasia of the gallbladder, biliary atresia, and hemochromatosis are part of the spectrum of hepatic disorders associated with MRS/MFS. 1,[13][14][15] Many patients require a Kasai portoenterostomy or liver transplantation at a very early age. 6,[16][17][18] Our patient had most of the gastrointestinal abnormalities seen in MRS/MFS, was fully dependent on PN, suffered from multiple episodes of central line-associated sepsis with bacterial translocation, and developed PN-associated liver disease.…”
Section: Discussionmentioning
confidence: 99%